2006
DOI: 10.1017/s1041610206003784
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of dementia in developing countries: an evaluation of costs of Alzheimer-type dementia in Argentina

Abstract: With the projected increase in the number of persons at risk for developing AD in emerging countries, the family cost of the disease will be significant. Dementia costs should be a matter of analysis when health policies are being designed in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
1
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(143 citation statements)
references
References 22 publications
2
131
1
9
Order By: Relevance
“…In a previous report, it was shown that caregiver burden in demented patient was mainly influenced by neuropsychiatric symptoms in Buenos Aires, Argentina (Allegri et al, 2007). A summary symptom burden was found to be correlated with caregiving burden.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a previous report, it was shown that caregiver burden in demented patient was mainly influenced by neuropsychiatric symptoms in Buenos Aires, Argentina (Allegri et al, 2007). A summary symptom burden was found to be correlated with caregiving burden.…”
Section: Introductionmentioning
confidence: 82%
“…The Clinical Dementia Rating (CDR) could not be related to caregiver burden in dementia patients (Mangone et al, 1993;Allegri et al, 2006). The Mini Mental Scale Examination (MMSE) was found to be related to caregiver burden in stroke and Parkinson's disease but that was not the case for mild or severe dementia (Thommessen et al, 2002;Allegri et al, 2007). However, a different measure of cognitive status (the revised Hasegawa Dementia Rating Scale) was found to be related to caregiver's burden in dementia (Nagatomo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is also emerging of the extent of the economic burden in middle-income countries (71)(72)(73)(74).…”
Section: Mortality Associated With Dementiamentioning
confidence: 99%
“…Allegri showed that the annual direct costs of patients with AD in Argentina increased with cognitive deterioration from US$3420.4 in mild AD to US$9657.6 in severe AD, and with institutionalization (US$3189.2 for outpatients vs US$14, 447.68 for those institutionalized) [3]. In LA, most direct costs were paid for by the family because social security was limited in this region.…”
Section: Economic Costs Of Dementia In Lamentioning
confidence: 99%